WHATSAPP-BASED E-LEARNING IMPLEMENTATION ON VALUES LEARNING PANCASILA IN CLASS V SD NEGERI 122351 INTRODUCTION - Sihombing, Chintani; Cui, Zhenyu; Karo Karo, Romaida; Aulia Nanda, Ficha; Samosir, Jusnita (International Conference on Health Science, Green Economics, Educational Review and Technology, 2020)
The problem in this study is in learning the subject matter of applying Pancasila values. The purpose of this study was to find out the application of Pancasila values through whatsapp-based e-learning by fifth grade students at SD Negeri 122351 Pematangsiantar which were applied at each student's home. This research is a field research, namely research carried out in the community. Based on the purpose of a research carried out, this research is included in descriptive research, because it aims to describe certain characteristics of a phenomenon and tries to describe what exists (it can be about conditions or relationships that exist, opinions that are growing, processes that are ongoing, consequences or effects that happening, or a trend that is developing). Data collection was carried out by interviews and documentation. The population in this study were students, teachers and parents of fifth grade students at SD Negeri 122351 Pematangsiantar. The sample in this study were 20 fifth grade students, 1 fifth grade teacher and 5 parents of fifth grade students at SD Negeri 122351 Pematangsiantar. In analyzing data, namely data collection, classifying data, explaining data and drawing conclusions. The results of this study indicate that fifth grade students at SD Negeri 122351 Pematangsiantar are able to apply Pancasila values at home through learning from WhatsApp. This was obtained from the results of interviews with parents of fifth grade students at SD 122351 Pematangsiantar